Magnesium-catalysed hydroboration of pyridines: Kinetic analysis and poly-pyridine dearomatisation. (8th January 2016) - Weetman, Catherine; Hill, Michael S.; Mahon, Mary F.
Graphical abstract: Kinetic analysis of the Mg-catalysed hydroboration of iso -quinoline with pinacol borane (HBpin) and studies of poly-pyridine dearomatisation, which are resistant to the hydroboration catalysis, have provided evidence that the catalysis proceeds via rate determining Mg–N/H–B metathesis of dearomatised pyridide anions. Abstract: A kinetic analysis of the hydroboration of iso -quinoline with pinacol borane (HBpin) and catalysed by a β-diketiminato magnesium n -butyl pre-catalyst has provided evidence that the reaction proceeds via rate determining Mg–N/H–B metathesis of a dearomatised iso -quinolide anion. The reaction rate is suppressed by increasing [ iso -quinoline] leading to the suggestion that catalytic turnover is also dependent on a pre-equilibrium involving dissociation of donor substrate molecules from the coordination sphere of the catalytic Mg centre. Stoichiometric reactions with a variety of poly-pyridine heterocycles have provided a range of magnesium derivatives of the dearomatised poly-pyridides either by alkyl or hydride transfer. The resistance of these latter species toward hydroboration is rationalised as a consequence of their additional coordinative stability providing corroborative evidence for the dissociative mechanism inferred from the kinetic analysis.